Pollutant Adsorbtion and Detection: Methyl‐Substituted α‐Cyclodextrin as Affinity Material for Storage, Separation, and Detection of Trichlorofluoromethane (Global Challenges 8/2018). Issue 8 (27th August 2018) - Ryvlin, Dimitrij; Girschikofsky, Maiko; Schollmeyer, Dieter; Hellmann, Ralf; Waldvogel, Siegfried R.
Abstract : The cover image depicts the hazard caused by chlorofluorocarbons such as CFC‐11, which are used, for example, as blowing agents for polyurethane foams, and the protective effect of the oligosaccharide, hexakis‐(2, 3, 6‐tri‐ O ‐methyl)‐ α ‐cyclodextrin, which is capable of binding CFC‐11 by supramolecular complexation and thus protecting the stratospheric ozone layer from the harmful trichlorofluoromethane. Further details can be found in article number1800057 by Ralf Hellmann, Siegfried R. Waldvogel, and co‐workers.